HUBUNGAN SIMTOM ANSIETAS DENGAN PENGGUNAAN ROKOK ELEKTRIK PADA MAHASISWA KEDOKTERAN - AMALIYAH HAQ; CUT MOURISA (JURNAL ILMIAH KOHESI, 2021)
Anxiety is a common psychiatric condition that often occurs and often not detected or treated in large populations. Severalstudies have shown high levels of psychological morbidity in college students around the world, especially related todepression and anxiety. Likewise, anxiety that occurs among medical students has a prevalence of 33.8%, which means thatone in three medical students globally has anxiety. The high level of anxiety in students caused some students to take it onsmoking behavior, including e-cigarettes. Some people claim that e-cigarettes or e-cigarettes have ingredients that canrelieve symptoms of anxiety. To find out whether there is a relationship between anxiety symptoms and e-cigarette use inmedical students. Analytical descriptive with cross sectional study approach to 183 medical students. The data of this studywere obtained from primary data using the Beck anxiety inventory questionnaire and the e-cigarette use questionnaire. Thenthe analysis was carried out using the Chi Square test. Results 47 (25.7%) Medical students who experience anxiety and usee cigarettes. The results of the Chi Square test showed that there was a significant relationship between the symptoms ofanxiety and the use of e-cigarettes in medical students with a value of P = 0.001 (p <0.05).